FACTORS ASSOCIATED WITH THE OCCURRENCE OF PRIMARY MULTIDRUG-RESISTANT TUBERCULOSIS IN MEDAN: Faktor Yang Berhubungan Dengan Kejadian Tuberkulosis Multidrug-Resistant Primer di Kota Medan - Hutomo, Rizky Aditya; Wahyuni, Chatarina Umbul; Sarumpaet, Sorimuda (Jurnal Berkala Epidemiologi, 2024)
Background: Tuberculosis (TB) treatment failure may lead to multidrug-resistant tuberculosis (MDR-TB). This failure can be detrimental to patients, not only causing death, but can also be transmitted to others, and those who are infected directly fall into the category of MDR-TB so that it can be referred to as primary MDR-TB. MDR-TB is the biggest problem in the prevention and eradication of TB worldwide. MDR-TB is a type of Mycobacterium tuberculosis resistance to at least the first two TB drugs of choice, including Isoniazid and Rifampicin. Purpose: This study aimed to determine the association between education, contact history, and knowledge regarding the occurrence of primary MDR-TB. Methods: This study used a cross-sectional study conducted at Community Health Center in Medan from November 2021 to February 2022. A total of 47 TB patients were selected for this study through purposive sampling methods. The dependent variable was primary MDR-TB occurrence while the independent variables consisted of several characteristics, namely education, contact history, and knowledge. The data were analyzed using chi-square. Results: in this study, sex  (p=0.56; PR=1.12; 95% CI= 0.30<1,12<4,14;) and education (p=0.40; PR=0.56; 95% CI= 0.14<0.56<2.19) was not associated, while age (p=0.02; PR=0.16; 95% CI=0.02<0.16<0.94), contact history (p<0.001; PR=7.94; 95% CI=2.11<7.94<29.83) and poor knowledge (p=0.01; PR=5.00; 95% CI= 1.31<5.00<18.96) were associated with an occurrence of primary MDR-TB. Conclusion: the prevalence of primary MDR-TB increases with age, contact history, and poor knowledge.